(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Soybean is frequently grown as a cash crop to assist farmers in improving their financial status. Charcoal rot is one of the most serious diseases of soybean crop. Therefore, the management of this disease is of utmost importance for enhanced production of soybean. In the present study, the samples for the isolation of pathogen and antagonist were collected from the soybean field. The isolated fungal isolate Gmax20 and Gmaxr2 were genetically identified as Macrophomina phaseolina Gmax20 and Trichoderma rugulosum Gmaxr2 by NCMR Pune. The results depicted that T. rugulosum Gmaxr2 reduced the development of M. phaseolina Gmax20 by 50.52 % as compared to the control. The mycoparasitic activity of Trichoderma rugulosum Gmaxr2 against Macrophomina phaseolina Gmax20 was evident from the compound and scanning electron microscope. Overall, the results suggest that T. rugulosum Gmaxr2 can be used as an effective biocontrol agent for the management of M. phaseolina Gmax20.